First experience of breast screening in the department of Tacuarembó - Buglione, Jorge; Horvarth, Jorge; Ferreira, Ciro (Cirugía del Uruguay, 1998)
Aim: Development of a breast screening program based on mammographical study in the department of Tacuarembó.